PENGARUH REKNSILIASI DATA, KAPASITAS SUMBER DAYA MANUSIA DAN SARANA PRASARANA TERHADAP KUALITAS LAPORAN KEUANGAN KEPOLISIAN DAERAH JAMBI - Eri Muspidra (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2023)
This research aims to evaluate and analyze the impact of data reconciliation, human resource capacity, and infrastructure on the quality of government financial reports within the Jambi Regional Police. The population that is the focus of this research is all Work Units in the Jambi Regional Police, totaling 32 Work Units. In this research, the sample selection method uses a purposive sampling approach, where samples are taken based on the researcher's subjective considerations which are adjusted to the research objectives. The type of data used is primary data, with data collection techniques through distributing questionnaires to respondents. A total of 96 questionnaires were sent to respondents, but only 86 were returned. Hypothesis testing is carried out using multiple linear regression tests. Based on the results of this research, it can be concluded that simultaneously there is a significant influence between data reconciliation variables, human resource capacity and infrastructure on the quality of government financial reports. Partially, the research results show that data reconciliation has a significant effect, human resource capacity has a significant effect, and infrastructure has a significant effect on the quality of government financial reports.